Microstructural evolution of ZA3 Alloy during Isothermal treatment - M.A.M., Arif; Mohd. Zaidi, Omar; Norhamidi, Muhamad; Syarif Junaidi, S Djalil (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.